Enhancing Women's Community Organization Financial Literacy Through Personal Financial Management Training - Warsitasari, Wahyu; Abin, Moh. Rois; Nadhirotus Shoidah, Nadia (Transformatif : Jurnal Pengabdian Masyarakat, 2024)
Individual well-being is intimately tied to financial knowledge. Higher financial literacy will influence how a person manages their finances. Individuals must have knowledge and comprehension of personal finance in order to make sound financial decisions. The purpose of this community service project is to: (1) educate participants on personal financial management and financial literacy. (2) Apply participants' skills and abilities in personal financial management practice to develop financial literacy. (3) Increase participants' financial knowledge following personal financial management training. For 35 women driving groups in Ngares Village, Trenggalek District, Trenggalek Regency, the community service technique employs a participatory training method. Community service activities on personal financial management training for women who own organizations in Ngares Village, Trenggalek District were efficiently executed. Women driving the organization in Ngares Village, Trenggalek District, have improved their financial literacy. Participants learnt new things about personal financial management, whereas those who had never learned before learned more.